Rancang Bangun Pengisi Baterai Portabel Berbasis Mikrokontroler Arduino - Giyantara, Andhika; Syarif, Muhammad; Rizqi Utami, Amalia (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The development of automotive technology, especially in electric vehicles, is accelerating. Electric vehicles utilize batteries as the main power source, making batteries a very vital component. Batteries function to store energy, but can experience a discharge if used without recharging. Therefore, a battery charging system is needed to reduce the possibility of discharge. One charging method that can be applied is constant voltage, where the voltage is kept constant from the beginning to the end of the charging process. To keep the voltage constant, a rectifier circuit and buck converter are used. The rectifier circuit functions to convert alternating voltage (AC) into direct voltage (DC), while the buck converter reduces the direct voltage (DC) and maintains it constant with control to regulate the switching on the MOSFET. In this research, the system is designed with an input voltage of 220 V which produces a constant output of 12 V. Control using PID allows duty cycle settings to reduce the direct voltage (DC). In a hardware test using a VRLA battery load, the test results showed that after charging for 25 minutes, the battery voltage increased from 11.49 V to 11.65 V.